Smart luggage / Muhammad Afiq Danial Mohd Suhaimi … [et al.] - Mohd Suhaimi, Muhammad Afiq Danial; Mohamad Zaffir, Nur Zahirah; Abu Hasim, Nurul Syaiyidatina; Norazlan, Norazlin; Abd Azis, Rafidah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
This study aims to create market innovation in manufacturing in the travel industry. Specifically, it investigates these problem statements which are “Are they someone who travels mainly for business?”, “Do they like to take long-term sightseeing trips?” and “Do they prefer more nature-based adventures?”. Each of these options will weigh into what kind of suitcase would suit their needs and be the most convenient for them on their trip. This study tries to bring innovative ideas to the tourism sector, maintain customer satisfaction by guaranteeing that the products match customer needs and ensuring that the employees have all of the resources they need to be as productive as possible. In this study, we estimated that polycarbonate is the option material since it is high-quality material that is impact resistant, waterproofing, and scratch resistant. This smart luggage also features a modern dresser-style drawer, a hangar-friendly bar and the ability to charge a smartphone. This study will result in producing the most beneficial product that will satisfy all customers, especially those who enjoy travelling. In addition, smart luggage can specialise in travel-friendly or luggage friendly, which secures the items during travel, and is the most beneficial and useful to travellers. In conclusion, we hope that this study will develop into the most popular luggage in Malaysia and throughout the world, while also being unforgettable due to its unusual and original idea in the future.